2014
DOI: 10.1152/jn.00700.2013
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of neuronal responses in cortical area MT across signal strengths and motion directions

Abstract: Multiple visual stimuli are common in natural scenes, yet it remains unclear how multiple stimuli interact to influence neuronal responses. We investigated this question by manipulating relative signal strengths of two stimuli moving simultaneously within the receptive fields (RFs) of neurons in the extrastriate middle temporal (MT) cortex. Visual stimuli were overlapping random-dot patterns moving in two directions separated by 90°. We first varied the motion coherence of each random-dot pattern and character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(43 citation statements)
references
References 51 publications
5
33
0
Order By: Relevance
“…Second, conceptually area MT appears to be operate at a stage of visual processing that is more involved with the extraction of features than the combination of features into invariant representations of objects (Fujita, 2002). MT’s emphasis on extraction is consistent with computational models (Adelson & Bergen, 1985; Joukes et al, 2014) and experimental data that reveal competitive interactions (Gaudio & Huang, 2012; Krekelberg & Albright, 2005; Krekelberg & van Wezel, 2013; Xiao et al, 2014), the weighing of evidence and counter-evidence (Duijnhouwer & Krekelberg, 2015), and segmentation of figure and ground (X. Huang, Albright, & Stoner, 2007; X.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Second, conceptually area MT appears to be operate at a stage of visual processing that is more involved with the extraction of features than the combination of features into invariant representations of objects (Fujita, 2002). MT’s emphasis on extraction is consistent with computational models (Adelson & Bergen, 1985; Joukes et al, 2014) and experimental data that reveal competitive interactions (Gaudio & Huang, 2012; Krekelberg & Albright, 2005; Krekelberg & van Wezel, 2013; Xiao et al, 2014), the weighing of evidence and counter-evidence (Duijnhouwer & Krekelberg, 2015), and segmentation of figure and ground (X. Huang, Albright, & Stoner, 2007; X.…”
Section: Discussionsupporting
confidence: 63%
“…If adaptation suppresses the output of the neurons in the surround, this would result in disinhibition of the neurons in the center and therefore post-adaptation enhancement (Wissig & Kohn, 2012). Similarly, rightward selective neurons in MT are commonly modeled as being inhibited by leftward selective MT neurons (Simoncelli & Heeger, 1998), and there is considerable evidence for more complex competitive interactions in MT neurons (Gaudio & Huang, 2012; Krekelberg & Albright, 2005; Xiao, Niu, Wiesner, & Huang, 2014). If, for instance, this inhibition falls away after adapting to leftward motion (i.e., the leftward preferring neurons undergo repetition suppression), then the rightward selective neurons could increase their response due to disinhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Work in our laboratory has shown that the direction tuning curves of MT neurons in response to overlapping random-dot stimuli moving transparently in two different directions can also be described as a weighted sum of the responses elicited by the individual stimulus components (Xiao et al, 2014;Xiao and Huang, 2015). When two stimulus components have different signal strengths in one feature domain, defined either by motion coherence or luminance contrast, MT neurons pool the stimulus component that has a stronger signal strength with a greater weight (Xiao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Work in our laboratory has shown that the direction tuning curves of MT neurons in response to overlapping random-dot stimuli moving transparently in two different directions can also be described as a weighted sum of the responses elicited by the individual stimulus components (Xiao et al, 2014;Xiao and Huang, 2015). When two stimulus components have different signal strengths in one feature domain, defined either by motion coherence or luminance contrast, MT neurons pool the stimulus component that has a stronger signal strength with a greater weight (Xiao et al, 2014). The response bias in area MT toward the stimulus component that has a stronger signal strength can be accounted for by a descriptive model of divisive normalization (Xiao et al, 2014), similar to the contrast normalization model used to describe neuronal responses in V1 (Carandini et al, 1997;Busse et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation